Next, the Campus Interview: An Elegy for Graduate Student Mothers - Rotolo, Susan (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
This article offers a frank and candid picture of a mother managing the ins and outs of academic study and a campus interview for a tenure-track position. It offers a creative interrogation into the cultural conversation following motherhood in graduate school and points honestly and openly to a variety of responses in the author’s experience. The article ultimately aims to make known the reality of campus visitsfor mothers and shed light on the cultural discomfort around the issues of academe and mothering.